Case Report: Serial Seizures Due to the Pesticide Poison Strychnine, Refractory to High Doses of Benzodiazepines - Aghabiklooei, Abbas; Abolmaali, Meysam (International Journal of Medical Toxicology and Forensic Medicine, 2019)
Drugs and poisons are the most common causes of new cases of seizure at emergency wards, a fact that can be easily missed unless physicians consider its likelihood in mind. In this report, we describe a case of recurrent seizures due to intentional ingestion of a pesticide poison (strychnine) that was refractory to very high doses of benzodiazepines and other anticonvulsants. Our patient suffered from 12 times tonic seizures and generalized muscular spasms, until he underwent anesthesia to control the seizures. Finally, he was discharged without any serious complications.